Probing Heterogeneous Degradation of Catalyst in PEM Fuel Cells under Realistic Automotive Conditions with Multi‐Modal Techniques. Issue 35 (29th July 2021) - Khedekar, Kaustubh; Rezaei Talarposhti, Morteza; Besli, Münir M.; Kuppan, Saravanan; Perego, Andrea; Chen, Yechuan; Metzger, Michael; Stewart, Sarah; Atanassov, Plamen; Tamura, Nobumichi; Craig, Nathan; Cheng, Lei; et al.
Abstract: The heterogeneity of polymer electrolyte fuel cell catalyst degradation is studied under varied relative humidity and types of feed gas. Accelerated stress tests (ASTs) are performed on four membrane electrode assemblies (MEAs) under wet and dry conditions in an air or nitrogen environment for 30 000 square voltage cycles. The largest electrochemically active area loss is observed for MEA under wet conditions in a nitrogen gas environment AST due to constant upper potential limit of 0.95 V and significant water content. The mean Pt particle size is larger for the ASTs under wet conditions compared to dry conditions, and the Pt particle size under land is generally larger than under the channel. Observations from ASTs in both conditions and gas environments indicate that water content promotes Pt particle size growth. ASTs under wet conditions and an air environment show the largest difference in Pt particle size growth for inlet versus outlet and channel versus land, which can be attributed to larger water content at outlet and under land compared to inlet and under channel. From X‐ray fluorescence experiments Pt particle size increase is a local phenomenon as Pt loading remains relatively uniform across the MEA. Abstract : Due to its high energy density, zero carbon emissions hydrogen is expected to be competitive in grid storage and heavy‐duty applications. Fuel cells are electrochemical technologies that convert hydrogen into electricity. The stack durability needs to be improved for broad deployment. This article explores the heterogeneous degradation of the catalyst material in fuel cells and shows how operating conditions and gas flow‐field design impact durability.